胸腺素β10在人肺腺癌细胞株A549中抑制细胞凋亡、促进细胞增殖机制研究 (Zhongguo Fei Ai Za Zhi, 2014)
BACKGROUND AND OBJECTIVE: Thymosin beta 10 (Tβ10) is one of β-thymosin family members, has a highly conserved polar 5 kDa peptides. This peptide is now regarded to be a small actin-binding protein and thereby induce depolymerization of the intracellular F-actin networks. Alteration of Tβ10 expression may alter the balance of cell growth, cell death, cell attachment and cell migration. Tβ10 also affects cell metastasis as well as proliferation, apoptosis and vascularization of cancer cells. But function of Tβ10 appear to be rather different between cancer cells, and the molecular mechanisms of β-thymosins to regulate cell apoptosis and proliferation in NSCLC (non-small cell lung cancer) cell lines are unclear. In this study, we used lung adenocarcinoma cell line A549, added Tβ10 or down-regulated the expression of Tβ10. We observed the change of apoptosis, proliferation and cell cyclin ability in A549 and the mechanisms underline them were also identified. METHODS: After A549 was treated with 100 ng/mL recombinant human Tβ10 or siTβ10, apoptosis rate of A549 and cell cycle distribution were detected by flow cytometry (FCM). CCK-8 assay was employed to determine the proliferation of A549. The mRNA level of P53, Caspase-3, Cyclin A and Cyclin E were determined by real-time PCR. The protein level of P53, Caspase-3, Cyclin A and Cyclin E were detected by Western blot. RESULTS: Add Tβ10 can inhibit the apoptosis and prompt the proliferation of A549. It can also increase the cell rates of S-phrase and G(2)/M-phrase, decrease the expression of P53 and Caspase-3, but increase the expression of Cyclin A and Cyclin E. Interferance of Tβ10 can prompt the apoptosis and inhibit the proliferation of A549. It can also increase the cell rates of G(0)/G(1)-phrase, increase the expression of P53 and Caspase-3, but decrease the expression of Cyclin A and Cyclin E. CONCLUSION: In lung cancer cell line, Tβ10 can inhibit the apoptosis by increase P53, drive cells into the S and G(2)/M-phase, prompt cell proliferation by increase the expression of Cyclin A and Cyclin E. Tβ10 may become a potential biomarker and therapy target for non-small cell lung cancer.